Nesting Ecology of West African Dwarf Crocodiles in a Heavily Disturbed Landscape in Chirehin, Ghana. (8th June 2021) - Amoah, Emmanuel; Danquah, Emmanuel; Perran Ross, James
Abstract : West African dwarf crocodiles ( Osteolaemus sp. nov. cf. tetraspis ) are among the most threatened crocodilians in the world due to unregulated hunting and habitat loss-related population decline . Despite this, many questions about their basic ecology remain unanswered and this inadequate data hampers effective dwarf crocodile management. We describe incubation temperature, nesting success, hatching rate, and clutch size of West African dwarf crocodiles. We monitored 18 nests from the 2017 and 2018 nesting seasons in the Chirehin Community Land—a highly disturbed agricultural matrix in the climatic transition zone of Ghana. We used Hobo tidbit® data loggers to monitor egg chamber temperature and the effect of ambient temperature on nest temperature. The daily mean incubation temperature recorded during the study was 30.7°C (±SD = 0.8°C, n  = 240, range = 28–33°C) and it is congruent with the reported value for the species. The findings from this study suggest a weak positive to no correlation between dwarf crocodile incubation temperature and ambient temperature indicating nest temperature is almost independent of ambient temperature. We found a mean clutch size of 8 eggs per nest (SD = ±2; range = 5–13; n  = 17) supporting previous reports that this genus has a low clutch size. The mean nesting success and hatching success across the two seasons were 77.8% and 75.3% (SD = ±41.9, n  = 18), respectively. Three nests were destroyed by flood and one by an unknown predator suspected to be a West African Nile monitor lizard. Generally, dwarf crocodiles selected forest patches within the highly disturbed landscape for nesting indicating the need to protect the remaining forest patches. Efforts should be made to repeat the study across this species' range for an improved understanding of its nesting ecology.